Inter-regional innovation cooperation and structural heterogeneity: Does being a rural, or border region, or both, make a difference?. (February 2020) - Hjaltadóttir, Rannveig Edda; Makkonen, Teemu; Mitze, Timo
Abstract: This paper analyses the determinants of inter-regional innovation cooperation in European knowledge networks. Our main goal is to assess whether structural heterogeneity in the context of the "urban-rural dichotomy" and international borders can explain differences in the regions' engagement in inter-regional innovation cooperation. We estimate a gravity equation to model innovation cooperation, proxied by inter-regional co-patent applications, as a function of region-specific context conditions as well as technological and geographical distance. Our data comprise dyadic information on 203 NUTS2 regions in 15 European countries (EU-15) for the year 2010. The empirical results show that the basic gravity mechanisms drive the direction and strength of innovation cooperation between EU regions; i.e., geographical distance acts as an impediment to inter-regional co-patent applications. Regarding the importance of structural heterogeneity, we find that pairs of rural regions have lower levels of innovation cooperation compared to urban regions. Similarly, border regions are generally disadvantaged compared to non-border regions in terms of the intensity of innovation cooperation. However, while the latter result points to a negative border effect, our gravity model estimates also show that pairs of border regions are more active in terms of close geographical innovation cooperation (e.g., through international cross-border cooperation), which partly compensates for the negative border effect. This finding not only holds for urban but also rural border regions and may reflect policy attempts to support border regions, e.g., by strengthening the level of international cross-border cooperation within the EU. Highlights: Gravity model approach to study inter-regional innovation cooperation in the EU-15. Focus on structural heterogeneity not observed by standard gravity analyses. Results point to an urban premium in collaboration and a negative border effect. Border regions compensate disadvantage via intensive close geographical cooperation. Result holds for urban and rural regions pointing to role of cross-border cooperation.